Reflections on the innovative city: examining three innovative locations in a knowledge bases framework - Tommi Inkinen (Journal of Open Innovation: Technology, Market, and Complexity, 2015)
This paper combines three location-based cases with literature background focusing on knowledge bases and cities. The paper considers the regional context of the city of Helsinki and its surrounding area (HMA). Analyzed cases include three specific locations highlighting urban form, connectivity and knowledge-intensive production. Conceptually innovative cities are experiencing extensive change as they transform and change in order to become competitive providers of first class living for highly skilled global work-force. The integration of spatial characteristics into analyses of knowledge intensiveness of cities brings forth new theoretical openings for urban analysis setting platforms for open innovation and economy. The paper focuses on extensive material resources collected in numerous projects. The data gives more reliable picture of the knowledge-intensive locations compared to single interviews or survey studies. The total data includes work and education statistics, stakeholder interviews and observation field work. Provided reflections are classified according to key issues presented in urban studies and economic geography.
Keywords: 650; Wissensintensives Unternehmen; Hochqualifizierte Arbeitskräfte; Wissenstransfer; Standorttheorie; Helsinki (Region); Finnland